Appealing perspectives of structural, electronic, mechanical, and thermoelectric properties of Tl2(Se, Te)Cl6 vacancy-ordered double perovskites. (December 2021) - Ali, Malak Azmat; Dar, Sajad Ahmad; AlObaid, Abeer A.; Al-Muhimeed, Tahani I.; Hegazy, H.H.; Nazir, Ghazanfar; Murtaza, G.
Abstract: We present thermoelectric properties such as the Seebeck coefficient, thermal conductivity, electrical conductivity, figure of merit, and power factor of Tl2 (Se, Te)Cl6 vacancy-ordered double perovskites obtained with use of the BoltzTraP code. For input files, structural and electronic properties were calculated with the full potential linearized augmented plane wave method within the Wien2k computational code. The mechanical and thermal parameters were computed for calculation of the lattice thermal conductivity. Both compounds were found to have indirect band gaps (2.976 eV for Tl2 SeCl6 and 3.037 eV for Tl2 TeCl6 ). The valence bands were observed to be flat, which results in large values of the Seebeck coefficient ( S ) of 183.50 μV/K for Tl2 SeCl6 and 185.49 μV/K for Tl2 TeCl6 at room temperature. In addition, positive values of S determined the p -type conductivity in these compounds. The power factor, figure of merit, and electrical conductivity were found to increase with temperature, while the thermal conductivity was found to decrease, hence confirming the semiconductor nature of Tl2 (Se, Te)Cl6 compounds as predicted by their electronic properties. The figure of merit of these compounds was found to be higher than that of conventional metal halide perovskites. This makes the compounds investigated potential candidates for thermoelectric applications involving halide perovskites. Highlights: Thermoelectric properties of Tl2 (Se, Te)Cl6 were calculated with use of classical Boltzmann transport theory. Tl2 (Se, Te)Cl6 perovskites were found to be semiconductors. The valence bands were observed to be flat, which results in high values of the Seebeck coefficient. The electrical conductivity, power factor, and figure of merit were found to increase with temperature. The figure of merit of these compounds was found to be higher than that of conventional metal halide perovskites.